1997
DOI: 10.1111/1523-1747.ep12337492
|View full text |Cite
|
Sign up to set email alerts
|

Tight Clustering of Extracellular BP180 Epitopes Recognized by Bullous Pemphigoid Autoantibodies

Abstract: Bullous pemphigoid is a blistering skin disease associated with autoantibodies against the BP180 antigen, a transmembrane component of the hemidesmosome. Anti-BP180 antibodies have been demonstrated to be pathogenic in a passive transfer mouse model. One extracellular site on human BP180 (MCW-1) was previously shown to be recognized by 50-60% of bullous pemphigoid sera. To facilitate the identification of additional autoantibody-reactive epitopes, recombinant forms of the BP180 ectodomain were generated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
285
2
15

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 294 publications
(309 citation statements)
references
References 33 publications
7
285
2
15
Order By: Relevance
“…18,19 In addition, several major antigenic sites have been identified within the N-terminal 45 amino acid stretch of NC16A, while the remaining 28 amino acids of NC16A were shown to have no BP-associated epitopes. 17 Several studies have confirmed that the serum levels of anti-COL17 NC16A autoantibodies correlate with the disease severity of BP. 20,21 In addition to these clinical observations, the pathogenicity of anti-COL17 NC16A IgG antibodies from BP patients was shown by in vitro study.…”
Section: Major Pathogenic Autoantigen: Type XVII Collagen (Col17)mentioning
confidence: 95%
See 1 more Smart Citation
“…18,19 In addition, several major antigenic sites have been identified within the N-terminal 45 amino acid stretch of NC16A, while the remaining 28 amino acids of NC16A were shown to have no BP-associated epitopes. 17 Several studies have confirmed that the serum levels of anti-COL17 NC16A autoantibodies correlate with the disease severity of BP. 20,21 In addition to these clinical observations, the pathogenicity of anti-COL17 NC16A IgG antibodies from BP patients was shown by in vitro study.…”
Section: Major Pathogenic Autoantigen: Type XVII Collagen (Col17)mentioning
confidence: 95%
“…5). 16,17 Epitope mapping using various fragments of COL17 has shown that sera from most BP patients recognize NC16A. 16 ELISA analysis using recombinant COL17 NC16A demonstrated that 94-96% of BP sera reacts to COL17 NC16A peptides.…”
Section: Major Pathogenic Autoantigen: Type XVII Collagen (Col17)mentioning
confidence: 99%
“…4). Four of these epitopes (NC16A1 through NC16A3) are also recognised by sera from patients with bullous pemphigoid and linear IgA disease 44,45 . In contrast, PG sera do not react with epitope NC16A4, which is a major target of autoantibodies in lichen planus pemphigoides 46,47 .…”
Section: Immunopathology and Diagnosismentioning
confidence: 99%
“…Previous studies have demonstrated that COL17 is the major autoantigen (autoAg) not only for BP but also for other pemphigoid disorders, including linear IgA bullous dermatosis (LAD), mucous membrane pemphigoid, pemphigoid gestationis and lichen planus pemphigoides 3 . The major epitopes for BP autoAbs tightly cluster within the juxtamembranous non-collagenous NC16A domain of COL17, and the majority of IgG autoAbs react with this region 6,7 . Passive transfer experiments of rabbit IgG 8 and autoAbs from BP patients 9 into wild-type (WT) or transgenic (Tg) neonatal mice have demonstrated pathogenic roles of antibodies (Abs) to the NC16A domain in blister formation.…”
mentioning
confidence: 99%